PENGUATAN NILAI-NILAI ASWAJA ALA KIAI HASYIM ASY’ARI DALAM PENDIDIKAN KONTRA-RADIKALISME - Nurkilat Andiono (Institut Keislaman Abdullah Faqih Gresik, 2021)
Abstract: KH. Hasyim Asy'ari is one of the leading ulama figures throughout the archipelago, his various thoughts have contributed greatly to the Islamic scientific knowledge, especially those related to the Ahlussunah wal Jama'ah which has recently been contested by various Islamic groups in Indonesia. This paper aims to review the concept of Aswaja according to KH. Hasyim Asy'ari was perceived as still relevant as an effort to stem radicalism (counter-radicalism). To study and understand the values of Aswaja of KH. Hasyim Asy'ari and his originality of thought were carried out by tracing his works related to Aswaja's understanding from various kinds of literature, both those written by him directly and his thoughts written by others. The research findings show that, first, the Aswaja concept of KH. Hasyim Asy'ari is a development of the Aswaja concept that was established by Abu Hasan al-Asy'ari and Abu Manshur al-Maturidi which is believed to be yet original as the teachings of Ahlussunnah wal Jama'ah which were practiced by the Prophet Muhammad SAW. Second, strengthening Aswaja's values in counter-radicalism education is taken from some of the core thoughts of KH. Hasyim Asy'ari, such as fikrah tawasuthiyah (moderate thinking), fikrah tasamuhiyah (tolerant thinking), fikrah ishlahiyah (reformative thinking), fikrah tathawwuriyah (dynamic thinking), and fikrah manhajiyah (methodological thinking).Keyword: Aswaja, KH. Hasyim Asy’ari, counter-radicalism.